Filming Frenchtown: Listening to and Learning From Storied Lives (LEARNing Landscapes, 2018)
This paper explores how teens used storytelling during a yearlong, extracurricular documentary film project. The project invited a group of 8-12 teens and university researchers to act as visual narrative inquirers in a local historic neighborhood. We explore the role of story, framing our project as a form of engaged pedagogy, and draw connections between storytelling and filming. We conclude that at the heart of the project is a shared dialogue. In this project, the scenario of filming enacted an encounter, and came to life through the stories the teens took in, and the stories they produced in response.
Keywords: visual inquiry; narrative inquiry; ethnocinema; informal learning; digital storytelling